Spacelike Hypersurfaces in Weighted Generalized Robertson-Walker Space-Times - Ximin Liu; Ning Zhang (Advances in Mathematical Physics)
Applying generalized maximum principle and weak maximum principle, we obtain several uniqueness results for spacelike hypersurfaces immersed in a weighted generalized Robertson-Walker (GRW) space-time under suitable geometric assumptions. Furthermore, we also study the special case when the ambient space is static and provide some results by using Bochner’s formula.